Isolation and typification of campylobacter fetus in the state of Rio de Janeiro, Brazil - Ramos, Auvanir de Almeida; Guida, Hélio Gustavo; Andrade, Vania Lucia Baeta (Pesquisa Agropecuaria Brasileira, 2014)
From 1972 to 1978,14 strains of Campylobacter fetus (Vibrio fetus) were isolated and typified, starting from a part of smegma, preputial washing, semen, vaginal mucus, stomach content of aborted fetuses of bovines with reproduction problems. The isolated samples strains were identified as Campylobacter fetus, subspecies fetus and intestinales.